A CASE OF SUBCUTANEOUS PHAEOHYPHOMYCOSIS CAUSED BY EXSEROHILUM SPECIES IN AN IMMUNOCOMPROMISED PATIENT - Koppada Rajasekhar; Anaparthy Usharani; Nirupama Padmaja Bondili; Ratna Harika Dusi; Perala Balamurali Krishna (Our Dermatology Online, 2013)
Phaeohyphomycoses are rare fungal infections, caused by dematiaceous fungi, manifested as cutaneous and subcutaneous infections, meningitis, sinusitis, keratitis, osteomyelitis and disseminated infection. This is a case report of a 45year old immuno compromised female on ART (Anti Retroviral therapy) presented with fever and generalized nodular lesions draining pus on face, hands, axilla, groin and labia majora since one month. Biopsy of the subcutaneous nodule on the lateral aspect of the thigh revealed septate fungal hyphae on 10% KOH (10% Potassium Hydroxide) mount. Fungal culture of the biopsy material on SDA (Sabouraud's Dextrose Agar) at 250C showed cotton wooly, dark gray to olivaceous black growth with black reverse and identified as dematiaceous fungi belonging to Exserohilum species by microscopy. The patient was put on Itraconazole 200mg BD in combination with Terbinafine 250mg BD for which she responded with healing of pustular lesions in two weeks and complete remission in two months..